KOORDINASI PENERAPAN KEBIJAKAN AEROTROPOLIS DI KECAMATAN KERTAJATI KABUPATEN MAJALENGKA - Ramdhani, Ryan; Nurasa, Heru; Utami, Sawitri Budi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2018)
The title of this research is Coordination of Aerotropolis Policy in Kertajati Sub-District, Majalengka District. This research is motivated by the issue of inter-organizational relations in the application of the Aerotropolis policy which is focuses on three aspects; availability of land in accordance with Majalengka District's regional policies, availability of human resource as workforce, and to minimize social conflicts by creating the direction social and cultural transition of communities affected by the development of Aerotropolis areas. Aerotropolis policies arise from the existence of policies from the central government concerning the establishment of airport's location in Kertajati sub district, Majalengka district, West Java. The location establishment of Kertajati Airport has opened many opportunities to West Java province so that the government of West Java can make a policy about "Peraturan Daerah Provinsi Jawa Barat nomor 13 tahun 2010 tentang Pembangunan dan Pengembangan Bandarudara Internasional Jawa Barat dan Aerocity Kertajati". The Aerotropolis in Kertajati District is expected to be able to boost the economy in West Java, especially Majalengka District. This Aerotropolis area is a very wide area and often reffered as Airport City or a new independent city that develops around the airport. According to Lie (2010) as a good criteria of coordination the author used factor that affect coordination such as planning, meeting point, partition of work, common goals, leadership, trust, and positive attitude. This research using qualitative descriptive method where data collection techniques are used literature and field study such as observation and interview. The result of this research show that inter-organizational relations in the application of the Aerotropolis policy not going well. This is shown by still unclear the partition of work and responsibilities, the unclear of the planning, and there is no mutual understanding in the application of policies.Keywords : Regional Development, Coordination, Aerotropolis, Kertajati